Disseminated Peritoneal Hydatidosis: A Case Report - Shashi Yadav; Prajwal Neupane; Kunal Pathak; Amit Bhattarai; Ujjwal Kumar Jha (Journal of Nepal Medical Association)
Hydatid disease or echinococcosis is caused by a tapeworm of the genus Echinococcus. Several cases of hepatic hydatid cysts are reported worldwide, but disseminated peritoneal hydatidosis with spontaneous rupture of cysts leading to ascites is a rare entity, and only a few instances in literature can be found. We would like to report case of disseminated peritoneal hydatidosis, which was secondary to the rupture of the primary hepatic hydatid cyst. Midline laparotomy with partial pericystectomy with removal of daughter cyst and peritoneal lavage was done.